Guidance for healthcare ethics committees - Hester, D. Micah; Schonfeld, Toby (Cambridge University Press, 2012)
Every accredited American hospital is required to have a mechanism for handling ethical concerns; most hospitals satisfy this requirement by constituting an institutional healthcare ethics committee (HEC), a pattern which is repeated in most western countries. This text provides definitive, comprehensive guidance for members of healthcare ethics committees who find themselves confronted with ethically challenging situations. Each chapter includes learning objectives, clinical case studies and questions to stimulate discussion among committee members. Particular emphasis is given to consultation, as this often presents the greatest challenges to committee members. Each chapter stands alone as a teaching module, as well as forming part of a comprehensive volume. Written and edited by nationally and internationally recognized experts in bioethics, this is essential reading for every member of a healthcare ethics committee.